Tissue testing as an index to the nutritional status of carnations - Peterson, Ralph C., author (Colorado State University. Libraries, 1960)
Soil testing is being used extensively as a means of regulating fertilizer programs for carnations, but this practice has serious limitations in the modern greenhouse where fertilization is accomplished by injecting dissolved fertilizer salts into the irrigation water. The nutrient reserve in the soil is small and not always a good indication of the nutrients available to plants. Soil nutrient levels maintained by dry applications of fertilizers are necessarily high and may reach excess proportions under a constant feeding program. Plant tissue testing, when correctly applied, will yield information which cannot be obtained in any other manner.

Comparison was made between the Spurway, Peech and English, and Thornton analytical methods. The Spurway tests were selected for nitrate and phosphorus determinations; the Peech and English method for calcium. Chemical methods were not found to be reliable for potassium determinations so these were made on a Beckman model B flame spectrophotometer.

Extraction with dilute acetic acid in a Waring blender offered a method which was fast and produced an extract with little variability. Several variations of the procedure were investigated. These included adjusting the concentration of the acid, time of extraction, and amount of activated carbon used as a decolorizing agent. The best results were obtained by using 10 grams of prepared carnation leaves, and covering with 200 ml of 2 per cent acetic acid solution, adding .25 grams (1/4 level teaspoon) of Darco G-60 activated carbon and extracting for three minutes, then filtering through Whatman No. 1 filter paper.

When this method was used, the extract was used full strength for the nitrate and calcium determinations, and was diluted 1 to 5 with distilled water for the potassium and phosphorus determinations.

Following the establishment of standard procedures, the nitrate, phosphorus, potassium, and calcium content of tissue from plants grown at five fertilizer levels in scoria were investigated, and an attempt was made to establish optimum ranges for the soluble fractions of the four nutrients in carnation tissue. The optimum levels in the plant extract are estimated to be: Nitrate – 10 to 20 ppm, Phosphorus – 2 1/2 to 4 ppm, Potassium - 50 to 70 ppm, Calcium – 125 to 175 ppm.

Tissue testing can be used to indicate accurately the differences among carnation plants receiving sub-optimal, optimal, and hyper-optimal nutrient levels for nitrate, phosphorus, and potassium. No calcium deficiencies or excesses were detected.

An evaluation of the system was made by obtaining 20 simultaneous tissue and soil samples from commercial greenhouses in the Denver, Colorado area. Tissue test results were compared to soil tests in an attempt to establish any correlation which might exist. Although a correlation was evident, a combined use of soil tests and tissue tests was indicated.

The tissue test results from the commercial samples showed a wide range of variation above and below the estimated optimums, as follows: Nitrate – 2 to 25 ppm, Phosphorus – 1/2 to 5 ppm, Potassium – 18 to 59 ppm, Calcium – 125 to 150 ppm. Accurate interpretations of tissue tests are more nearly possible if amounts of available nutrients in the soil are known. When phosphorus is high in the tissue, the excess is caused by high amounts of phosphorus in the soil, or low amounts of nitrate in the soil, or a combination of the two conditions. Accuracy in prescribing corrective measures depends on this knowledge. Correct interpretation of any combination of tissue test results is enhanced by accompanying soil tests.

Different light intensities and time of day affected nitrate content of immature carnation leaves, but did not significantly affect nitrate content of mature leaves. Date of sampling or day length between January and May had no apparent effect on nitrate content of mature carnation leaves.
Keywords: Carnations